Fragmented Authority and Overlapping Jurisdiction in Coastal Permitting: A Case Study of Sea Fence Construction - Didi Nursidi (International Journal of Science Education and Cultural Studies, 2026)
Coastal zones hold a crucial role in maintaining ecological stability, supporting economic livelihoods, and safeguarding the welfare of nearby communities. Yet the governance of coastal space in Indonesia remains constrained by persistent institutional fragmentation and inconsistent regulatory norms. This study examines how regulatory misalignment emerges within coastal spatial licensing practices, using the construction of a sea barrier in the coastal waters of Tangerang Regency as the principal empirical case. Unlike earlier studies that mainly discuss broad policy arrangements or governance systems in general terms, this research focuses closely on how differences in regulatory interpretation appear during concrete licensing procedures. A qualitative approach guides the inquiry, combining normative legal analysis with a governance perspective to identify the relationship between regulatory design and institutional conduct. The findings indicate that fragmented regulations, overlapping authority among agencies, and weak interinstitutional coordination together generate inconsistencies that weaken the credibility of the permitting process. These conditions create legal uncertainty and increase the likelihood of disputes over coastal spatial utilization. This article offers a case-oriented analysis of how interactions between regulation and institutions influence the outcomes of coastal licensing, and it contends that building more coherent and sustainable coastal governance in Indonesia requires stronger regulatory alignment, deeper institutional collaboration, and clearer policy guidance.